Utilization of Blood Flow Restriction Therapy with a Former Triathlete After Total Knee Arthroplasty: A Case Report - Christopher Keating; Stephanie Muth; Cameron Hui; Lisa T Hoglund (North American Sports Medicine Institute, 2024)
# Introduction and Purpose Knee osteoarthritis (OA) is a common condition that limits function and reduces quality of life. Total knee arthroplasty (TKA) is a surgical procedure that replaces the joint surfaces to address anatomical changes due to knee OA. While TKA improves symptoms and function, postoperative impairments are common, including reduced quadriceps strength. Blood flow restriction (BFR) may be a viable option for patients following TKA, as it can improve strength with a minimal amount of joint loading compared to traditional strength training. The purpose of this case report is to describe the impact of BFR use in an individual after TKA, employing pain measurements, quantitative sensory testing, patient-reported outcome measures, physical performance tests, and muscle strength and power testing to explore potential treatment effects and identify potential predictors of response for future studies. # Case Description A 49-year-old former female triathlete with a history of knee injury and arthroscopic surgery underwent a right TKA and sought physical therapy (PT) due to pain, limited range of motion (ROM), and knee instability during weight bearing activity. PT interventions included manual therapy, gait training, and a home program. Despite participating in supervised PT, she had persistent pain, ROM deficits, and muscle weakness 16 weeks following TKA. BFR was incorporated into her home program, 16-weeks postoperatively. The Short Form McGill Pain Questionnaire-2 (SF-MPQ-2) and Numeric Pain Rating Scale (NPRS) were used to measure pain. Quantitative sensory testing included pressure pain threshold (PPT) and two-point discrimination (TPD) to measure change in sensory perception. Patient-reported outcome measures to assess perceived physical function were the Knee injury and Osteoarthritis Outcome Score (KOOS) and the KOOS- Joint Replacement (KOOS-JR). Physical performance was measured through the 30-second fast walk test (30SFW), timed stair climb test (SCT), 30-second chair standing test (CST), and the timed up and go (TUG). Knee ROM was assessed through standard goniometry. Knee extensor and flexor muscle strength and power were measured with an instrumented dynamometer for isokinetic and isometric testing, generating a limb symmetry index (LSI). # Outcomes Pain and quantitative sensory testing achieved clinically meaningful improvement suggesting reduced sensitivity during and after BFR utilization. Perceived physical function and symptoms significantly improved, particularly in sports and recreation activities, and were best captured in the KOOS, not the KOOS-JR. Physical performance reached clinically meaningful improvement in walking speed, chair stand repetitions, and timed stair climb tests after BFR. Isokinetic and isometric strength and power in knee extensors and flexors increased significantly after BFR compared to the uninvolved leg as determined by LSI. # Discussion In this case, BFR appeared to be a safe and well-tolerated intervention. The results suggest potential benefits in terms of increased function, strength, power, and reduced pain in this specific person after TKA. Comprehensive pain and sensory assessments alongside clinical measures may help identify suitable patients for BFR after TKA. The KOOS-Sport & Recreation subscale may be more responsive to monitor functional recovery compared to the KOOS-JR, possibly due to the subject's athletic background. # Level of Evidence 4